Uganda's forgotten emergency the unhol y terror of the Lord's Resistance Army. - Integrated Regional Information Networks (Nairobi, Kenya : IRIN, 2004)
An interactive CD containing a short documentary and electronic copi es of special reports, released on the IRIN website, concerning the cri sis in northern Uganda.
Latest issue consulted
Keywords: Lord's Resistance Army; Civil war -- Uganda; Children and war -- Uganda